CLINICAL EVALUATION OF THE DYNAMICS OF CHANGES IN THE LEVEL OF ORAL HYGIENE IN PATIENTS WITH DENTAL CARIES OF MODERATE INTENSITY DURING THE APPLICATION OF A THERAPEUTIC AND PREVENTIVE COMPLEX - Goncharuk, S.V. (World of Medicine and Biology, 2025)
The study was devoted to evaluating the impact of a multi-component therapeutic-preventive complex on clinical indices of oral hygiene in young adults exhibiting moderately intensive dental caries. Forty-five patients aged 18–32 years were allocated to a comparison group receiving standard professional care and a main group who, in addition to standard care, followed a one-month home-use therapeutic-preventive complex regimen. Oral hygiene status was assessed at baseline and at 6, 12, and 24 months using the Silness-Löe and Stallard indices. The therapeutic-preventive complex produced a progressive decline in both indices over 24 months, whereas the comparison group showed no significant change. No adverse effects or unfavourable trends were recorded. These findings demonstrate that adjunctive use of the therapeutic-preventive complex significantly enhances long-term plaque-control outcomes beyond those achieved by professional hygiene alone, supporting its inclusion in personalised preventive protocols for patients with moderate caries activity.
Keywords: oral hygiene indices; remineralisation; therapeutic-preventive complex; dental caries; young adults